The Performance of the Pup Hacking Show Essential Philosophical Messages of Javanese Ethnic Life - Bambang Panca Syahputra; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2023)
Philosophical and philosophical are concerned with the values, assumptions or perceptions built by community members in their life journey. Philosophical and philosophical understood through things that are hidden and stated explicitly. Philosophical and philosophical in the text of Wayang Kulit can be analyzed through the use of transcribed speech language, so that the philosophical and philosophical in the text of Wayang Kulit are latent, therefore, the study of appraisal discourse analysis is to evaluate and interpret this philosophical form. Philosophical understanding can be interpreted as aspects of language that are philosophically charged. Language which is material that is charged, philosophically, there are aspects of language that are processed or formed by philosophies. Wayang kulit performance art as a tradition that combines various elements of art such as: the art of music, sound, dance and acting. This study uses a qualitative research method with research data which is text data of Wayang Kulit. The results of wayang kulit are obtained through the characteristics of the characters, moral messages and noble values, virtues, conveying religious dogmas, as well as the function of wayang as entertainment for wayang audiences and the public. Philosophical message as a philosophy of life, a positive attitude identified as the identity of the Javanese which is a philosophy that includes: a) philosophical as a philosophy of positive attitude, b) philosophical as a philosophy of patience, c) philosophical as a philosophy of truth, and d) philosophical as a philosophy moral attitude